Neandertals' large lower thorax may represent adaptation to high protein diet. Issue 3 (12th March 2016) - Ben‐Dor, Miki; Gopher, Avi; Barkai, Ran
ABSTRACT: Humans are limited in their capacity to convert protein into energy. We present a hypothesis that a "bell" shaped thorax and a wide pelvis evolved in Neandertals, at least in part, as an adaptation to a high protein diet. A high protein diet created a need to house an enlarged liver and urinary system in a wider lower trunk. To test the hypothesis, we applied a model developed to identify points of nutritional stress. A ratio of obligatory dietary fat to total animal fat and protein sourced calories is calculated based on various known and estimated parameters. Stress is identified when the obligatory dietary fat ratio is higher than fat content ratios in available prey. The model predicts that during glacial winters, when carbohydrates weren't available, 74%−85% of Neandertals' caloric intake would have had to come from animal fat. Large animals contain around 50% fat calories, and their fat content is diminished during winter, so a significant stressful dietary fat deficit was identified by the model. This deficit could potentially be ameliorated by an increased capability to convert protein into energy. Given that high protein consumption is associated with larger liver and kidneys in animal models, it appears likely that the enlarged inferior section of the Neandertals thorax and possibly, in part, also his wide pelvis, represented an adaptation to provide encasement for those enlarged organs. Behavioral and evolutionary implications of the hypothesis are also discussed. Am J Phys Anthropol 160:367–378, 2016. © 2016 Wiley Periodicals, Inc.